CITRONELLAL FROM CITRONELLA OIL BY WAY OF VARYING THE MIXING VELOCITIES AND THE ADDITIONS OF SODIUM BISULFITE - Muyassaroh, Muyassaroh (Jurnal Teknik Kimia, 2011)
At present the efforts to develop the cultivation of citronella oil has been given special attentionby the Indonesian Government. From various kinds of volatile crop kinds, one that is potential to bedeveloped is fragrant lemon grass. The fragrant lemon crops, fragnant lemongrass, which is a grasscrop which belongs to the group called Cymbogon nardus, is one that has great potensial to bedeveloped, The Technology used to produce volatile oil consist of 3 methods: pressing, solventextraction, and distillation. This research aims is to isolation Citronellal from Citronella Oil. In thisresearch the method used was refining the vapour and the water, followed by isolating citronellal fromcitronella oil and adding natrium bisulfite solution. This addition was aimed at acquiring the maximumlevel of citronellal that could be used as an active material for termiside or bakterial medicines. Theresearch result showed that the best quality of citronella was acquired when the Natrium Bisulfiteaddition was 20 gram, and the mixing velocity 150 rpm, producing 40.26% level of geraniol with adensity of 0,8867 gram/ml.Key words: Isolation, Natrium Bisulfite, Cymbopogan Winterianus, Sitronellal